Assessment of Business Aviation OCCs' Capacity Issues. (2017) - Pazourek, Michal; Václavík, Vojtěch
Abstract: Flying used to be a phenomenon of big airliners. It is now an ever-growing reality to see air carriers operating small aircraft too. Business jets are today frequent visitors to worldwide airspaces and airports. By gradual upgrades of the equipment (both aircraft and infrastructure) the character of business aviation changes significantly its nature. From the perspective of flight preparation and flight planning these flights range between the most complicated ones. In the business aviation community little attention is often paid to the importance of dimensioning their operation control centers (OCC). This paper shows typical capacity issues and available solutions to help optimize the OCCs capacity setup.